2012
DOI: 10.3233/wor-2012-0510-2675
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the strain on employees in the retail sector considering work-life balance

Abstract: Many companies currently strive to support their employees' work-life balance through appropriate measures in order to improve employees' loyalty towards the company and to recruit new employees. In this context, flexibility in the area of working times is a measure that can influence employees' private lives immensely. This is why the individualisation of working time arrangements has been accorded high importance in current discussions on work-life balance. In this area, best practice examples can be found s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Earlier studies of the retail sector based on the survey data of shift work have indicated difficulties in work-life balance or in sleeping [20][21][22][23] . In this study, we lacked assessment of The specific interest of this study was to compare part-time vs. full-time employees since part-time work is rare in the health care sector 14) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies of the retail sector based on the survey data of shift work have indicated difficulties in work-life balance or in sleeping [20][21][22][23] . In this study, we lacked assessment of The specific interest of this study was to compare part-time vs. full-time employees since part-time work is rare in the health care sector 14) .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of the retail sector based on the survey data of shift work have indicated difficulties in work-life balance or in sleeping 20 23 ) . In this study, we lacked assessment of such outcomes and therefore focused on establishing the codification for working hour characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HJP employees engage freely and willingly in their duties, such that successful task completion results in pleasure for them. Sales associates with HJP are devoted to their work and to their work–life balance (Zülch et al , 2012). As a result, HJP consistently demonstrates positive outcomes in the literature (Vallerand and Houlfort, 2003).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…This, in turn, results in a sense that the job has control over the person. As a result, OJP associates engage in compulsive work activity, which increases work–life balance tensions, further minimizing non-work activity and draining valuable self-control resources (Zülch et al , 2012). The depleted self-control resources increase the likelihood that associates will engage in negative work behaviours.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%